2020
DOI: 10.1021/acs.jctc.0c00603
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects with Frozen-Density Embedding in Real-Time Time-Dependent Density Functional Theory Using Localized Basis Functions

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policy If you believe that this document breaches… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 127 publications
(230 reference statements)
0
38
0
Order By: Relevance
“…However, recent advances have shown that there is interest in accelerating RT-TDDFT calculations and Ehrenfest molecular dynamics (EMD) via DFT embedding approaches. [48][49][50][51][52][53][54]…”
Section: Subsystem Dft-based Embeddingmentioning
confidence: 99%
“…However, recent advances have shown that there is interest in accelerating RT-TDDFT calculations and Ehrenfest molecular dynamics (EMD) via DFT embedding approaches. [48][49][50][51][52][53][54]…”
Section: Subsystem Dft-based Embeddingmentioning
confidence: 99%
“…The Frozen Density (FDE) 25,33,34,73 and Block-Orthogonalized Manby-Miller embedding (BOMME) approaches 62 , and their extension to the rt-TDDFT framework has been described in previous works 50,65 . In this Section, after brief recapitulation of the rt-TDDFT method, we will outline analogies and differences of rt-FDE and rt-BOMME approaches.…”
Section: A Theoretical Backgroundmentioning
confidence: 99%
“…The code implementing the rt-FDE in the Psi4Numpy framework used in this work is part of the PyBertha package 50,90,91 (revision 3c752072). The code implementing the (rt-)BOMME approach is under version control (Git) but does not yet have a public release version (one is envisaged for 2022).…”
Section: B Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Density embedding schemes were generalized to excited electronic states by linear-response as well as real-time TD-DFT [41][42][43][44][45][46] and applied for calculations of a number of spectroscopic properties, including for some impressively large systems with multiple chromophores. [47][48][49][50][51][52] But unlike these static calculations, to the best of our knowledge, there is only one report of using density embedding methods for simulating NA processes in a dynamic manner using Ehrenfest NA molecular dynamics (MD) with real-time TD-DFT. 29 In this work, we combine the power of the subsystem DFT with the practicality of the ∆SCF method to obtain excited electronic states.…”
Section: Introductionmentioning
confidence: 99%